Pengaruh Free Cash Flow, Market to Book Ratio dan Firm Size Terhadap Cost Of Equity Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2024 - Dwi Syahlani; Chandra Situmeang (STKIP Subang, 2025)
This study aims to analyze the influence of Free Cash Flow (FCF), Market to Book Ratio (MBR), and Firm Size on the Cost of Equity (CoE) in manufacturing companies listed on the Indonesia Stock Exchange in 2024. Cost of Equity is a key component of a company's capital structure, representing the expected return demanded by investors as compensation for risk. Amid global economic uncertainty and the increase of Bank Indonesia's benchmark interest rate in 2024, companies are required to manage their capital structure efficiently. This research uses a quantitative approach with secondary data derived from companies' annual financial reports. The sample was determined using purposive sampling, resulting in 171 manufacturing companies. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The dependent variable, Cost of Equity, is measured using the Capital Asset Pricing Model (CAPM), while the independent variables are Free Cash Flow, Market to Book Ratio, and Firm Size. The results show that Free Cash Flow has a negative effect on Cost of Equity, Market to Book Ratio has a negative effect, and Firm Size has a negative effect on Cost of Equity. Simultaneously, these three independent variables significantly influence Cost of Equity. These findings suggest that manufacturing firms need to consider their cash flow availability, market valuation, and scale of operations when making strategic decisions regarding their capital structure.